2022
DOI: 10.3389/fgene.2022.885589
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Severe Gonadal Dysgenesis Causing 46,XY Disorder of Sex Development Due to a Novel NR5A1 Variant

Abstract: Mutations in the nuclear receptor subfamily 5 group A member 1 (NR5A1) are the underlying cause of 10–20% of 46,XY disorders of sex development (DSDs). We describe a young girl with 46,XY DSD due to a unique novel mutation of the NR5A1 gene. An 11-year-old subject, raised as a female, was noticed to have clitromegly. She looked otherwise normal. However, her evaluation revealed a 46,XY karyotype, moderate clitromegly but otherwise normal female external genitalia, undescended atrophied testes, rudimentary uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The novel c.64G > T (p.G22C) mutation reported in the present study is a missense mutation, which reportedly accounts for 58% of NR5A1 mutations [6]. The p.G22C is located in the DBD, which is one of three domains in NR5A1, and previous studies have reported this as the location for multiple mutations in patients with 46, XY DSD [6, 20,23,24]. A previous study identi ed a G35E substitution in the DBD region in a patient with 46, XY DSD presenting adrenal insu ciency along with moderately severe gonadal dysplasia, indicating that this variation results in serious adverse effects on NR5A1 function [20].…”
Section: Discussionmentioning
confidence: 58%
“…The novel c.64G > T (p.G22C) mutation reported in the present study is a missense mutation, which reportedly accounts for 58% of NR5A1 mutations [6]. The p.G22C is located in the DBD, which is one of three domains in NR5A1, and previous studies have reported this as the location for multiple mutations in patients with 46, XY DSD [6, 20,23,24]. A previous study identi ed a G35E substitution in the DBD region in a patient with 46, XY DSD presenting adrenal insu ciency along with moderately severe gonadal dysplasia, indicating that this variation results in serious adverse effects on NR5A1 function [20].…”
Section: Discussionmentioning
confidence: 58%
“…The novel c.64G > T (p.G22C) variant reported in the present study is a missense variant, which reportedly accounts for 58% of NR5A1 variants [ 6 ]. The p.G22C substitution is located in the DBD, which is one of three domains in NR5A1, and previous studies have reported this as the location for multiple variants in patients with 46,XY DSD [ 6 , 22 , 24 – 26 ]. A previous study identified a G35E substitution in the DBD region in a patient with 46,XY DSD presenting adrenal insufficiency along with moderately severe gonadal dysgenesis, indicating that this variation results in serious adverse effects on NR5A1 function [ 22 ].…”
Section: Discussionmentioning
confidence: 99%